Determining the Financial Solvency Level of Insurance Companies by Insurance Branches - Firouzi, Melika; Emamverdi, Ghodratollah; Hamidian, Mohsen (Management Strategies and Engineering Sciences, 2025)
This study aims to assess the financial solvency levels of insurance companies across different insurance branches by comparing solvency margin ratios (SMR) calculated using regulatory coefficients and actuarial risk assessments. The study employs a quantitative research design, analyzing the financial solvency of eight major insurance companies operating across multiple branches, including life, health, property, liability, aviation, and marine insurance. Data were collected from publicly available financial reports, solvency disclosures, and actuarial evaluations, following the solvency assessment guidelines outlined in regulatory frameworks such as Solvency I and Solvency II. The solvency margin ratio was calculated using the formula SMR = Available Capital ÷ Required Capital, with comparative analysis conducted to evaluate differences between regulatory and actuarial assessments across insurance branches. Descriptive analysis, ratio comparisons, and sensitivity analysis were employed to interpret the results. The results indicate significant discrepancies between regulatory and actuarial solvency assessments, with life insurance demonstrating the highest solvency ratios and aviation and marine insurance exhibiting the lowest solvency levels. The findings suggest that regulatory solvency assessments may underestimate financial risks in high-risk branches, whereas actuarial assessments provide a more comprehensive risk-sensitive evaluation. Companies with diversified portfolios and strong capital reserves generally demonstrated higher solvency ratios, emphasizing the importance of risk management and capital adequacy strategies in maintaining financial stability. The study highlights the necessity for a more refined regulatory framework that aligns with actuarial risk assessments to ensure accurate solvency evaluations and financial resilience. Insurance companies should integrate both regulatory and actuarial solvency models to enhance financial risk management, particularly in high-risk branches such as aviation and marine insurance, to strengthen financial sustainability.